A modified Leslie-Gower-type predation model considering collaboration between predators - González Olivares, Eduardo (2021)
The interactions between predators and their prey are one of the most important aspects in the dynamics of food chains or trophic webs. Usually, this relationship in the real world is influenced by various behaviors, both from prey and  predators. Collaboration or cooperation between predators is one of those behaviors, which has received less attention than other behaviors of predators, such as competition between them. In this work, we will model the cooperation between predators to capture (or consume) their favorite prey using a recent proposition that modifies the linear functional response of the Leslie-Gower model. We show that this modified model has richer dynamics than the original, obtaining varied results. Among the main ones, populations can oscillate around a point where population sizes are fixed.